Export, a practical guide - Harlaar, Marlies, ....-; Oudehand, Michiel, ....-; De Leeuw, Otto, ....- (Groningen : Noordhoff, 2012)
Many entrepreneurs at some point ask themselves the question: ‘Should I go into the export business?' Or perhaps the question is, ‘I have been exporting for some time now, but have I been doing it as well as I could?' Do you want to know how to get the most from export opportunities? This textbook offers a practical guide to successful exporting. Moreover, it is immediately applicable to your own business situation. This practice-based English-language textbook will teach you in a logical and well-structured way how to analyse export opportunities in a number of foreign markets, select the most suitable country to which to export, and how to create a simple export plan. With the aid of a large number of checklists, assignments and practical examples you will quickly master the skills needed to succeed in the export business. You will find the checklists and the answers on www.export.noordhoff.nl. Export, a practical guide is intended for students in vocational education as well as for starting exporters—not just those in large companies. Small businesses have export opportunities as well. Companies that are already exporting goods or services can equally benefit from this textbook.
Keywords: Handel -- Export; Internationale handel